2000
DOI: 10.1021/jm9903388
|View full text |Cite
|
Sign up to set email alerts
|

Diamino Benzo[b]thiophene Derivatives as a Novel Class of Active Site Directed Thrombin Inhibitors. 5. Potency, Efficacy, and Pharmacokinetic Properties of Modified C-3 Side Chain Derivatives

Abstract: A systematic investigation of the structure-activity relationships of the C-3 side chain of the screening hit 1a led to the identification of the potent thrombin inhibitors 23c, 28c, and 31c. Their activities (1240, 903, and 1271 x 10(6) L/mol, respectively) represent 2200- and 2900-fold increases in potency over the starting lead 1a. This activity enhancement was accomplished with an increase of thrombin selectivity. The in vitro anticoagulant profiles of derivatives 28c and 31c were determined, and they comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Indeed, several potent inhibitors have been identified that include P1 groups such as aminoalkyl, aminocyclohexyl [137,187,188], aminopyridine [32,138,153,185,189], aminopyridazine [185], aminopyrimidine [185], aminopyrazine [185], benzamidrazone [190,191], thienylamidine [133], azaphenylalanine [192], 4,5,6,7-tetrahydro-1,3-benzothiazol-2-amine, 4,5,6,7-tetrahydro-2H-indazole and 2-imino-4,5,6,7-tetrahydro-1,3-benzothiazol-3(2H)-yl-amine [193]. Furthermore, there are also a few examples of neutral P1 moieties such as benzothiophene and hydroxybenzothiophene [194][195][196], cyclohexylmethyl, benzyl and dichlorobenzyl [197], 3-chlorobenzyl and 2-oxyacetamide-5-chlorobenzyl [38,198], phenol [33], tryptophan [199] and 6-fluorotryptamine [200]. As one of the most recent examples, screening of a fragment-based compound library also resulted in the discovery of thrombin-binding fragments with a nonbasic P1 motif [201].…”
Section: New Inhibitors -Old Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several potent inhibitors have been identified that include P1 groups such as aminoalkyl, aminocyclohexyl [137,187,188], aminopyridine [32,138,153,185,189], aminopyridazine [185], aminopyrimidine [185], aminopyrazine [185], benzamidrazone [190,191], thienylamidine [133], azaphenylalanine [192], 4,5,6,7-tetrahydro-1,3-benzothiazol-2-amine, 4,5,6,7-tetrahydro-2H-indazole and 2-imino-4,5,6,7-tetrahydro-1,3-benzothiazol-3(2H)-yl-amine [193]. Furthermore, there are also a few examples of neutral P1 moieties such as benzothiophene and hydroxybenzothiophene [194][195][196], cyclohexylmethyl, benzyl and dichlorobenzyl [197], 3-chlorobenzyl and 2-oxyacetamide-5-chlorobenzyl [38,198], phenol [33], tryptophan [199] and 6-fluorotryptamine [200]. As one of the most recent examples, screening of a fragment-based compound library also resulted in the discovery of thrombin-binding fragments with a nonbasic P1 motif [201].…”
Section: New Inhibitors -Old Principlesmentioning
confidence: 99%
“…However, only some chlorobenzyl-based inhibitors and a few hydroxybenzothiophene derivatives such as inhibitor 42 (K i = 0.3 nM; Fig. 13) [194][195][196] exhibited low-nanomolar inhibition constants. Recently, a new series of thrombin inhibitors containing D-tyrosine at the P1 position, was identified by a novel computer-assisted multiparameter optimization approach [37] based on a new type of algorithm developed by M. Thürk (Matrix Advanced Solutions Germany GmbH).…”
Section: New Inhibitors -Old Principlesmentioning
confidence: 99%
“…Optimization resulted in compounds, such as 115 (K i =0.3 nM) and 116 (K i = 0.5 nM), which were highly potent in clotting assays in vitro. In contrast, these inhibitors suffered from relatively poor in vivo efficacy due to rapid and extensive distribution in various tissues making them less available to inhibit thrombin in plasma [156,157].…”
Section: Inhibitors Of Other Structural Typementioning
confidence: 99%
“…1-4 For example, the benzofuran moiety is found in antidepressant (-)-BPAP, 5 angiotensin II inhibitors, 6 5-lipoxygenase inhibitors, 6 nerokinin-2 receptor antagonist, 7 cathepsin K inhibitors, 3 and calcium entry blockers. In addition, there are also many benzofuran-containing natural products including (−)-concentricolide, 8 (+)-frondosin B 9 and the eupomatenoid family.…”
mentioning
confidence: 99%